Limits on Exoneration from Responsibility in International Law: Amnesties, Selection and Priorization of Cases in National Jurisdiction - Sebastián Machado Ramírez (ACDI: Anuario Colombiano de Derecho Internacional, 2014)
Much has been said about the legal tools that a State has to confront a process of transitional justice. Traditionally, international literature has discussed the content of the “truth, justice and reparation” standards. Notwithstanding, little attention has been paid to the legal sources that may limit or permit the partial preclusion of wrongfulness in transitional justice mechanisms. This preclusion of wrongfulness may be part of a prosecutorial policy of prioritization and selection of cases, which may be in turn linked to partial amnesties or pardons. The objective of this article is to study three regulatory frameworks in international law: 1) international human rights law; 2) international humanitarian law; and 3) international criminal law. A close look reveals that no international instrument requires that a State investigates every case related to the armed conflict. In general terms, international law prohibits the adoption of blanket amnesties, but allows the State to select and prioritize its cases, without punishing the partial preclusion of wrongfulness of some of the perpetrators.